Gastroduodenal Intussusceptions in An Adult: Report of A Case. - Jerry G. Makama; Peter P. Abur; Ekundayo S. Garba; Adamu Ahmed; Lawal Khalid (Archives of Clinical and Experimental Surgery, 2012)
Gastroduodenal intussusceptions are an uncommon condition usually caused by the prolapse of a gastric tumor into the duodenum with subsequent invagination of a portion of the stomach wall. The diagnosis of adult intussusceptions can be delayed because it occurs infrequently and is nonspecific. The differential diagnosis of intermittent symptoms of pyloric stenosis in adults should include gastroduodenal intussusceptions.A rare case of this condition associated with a pedunculated gastric tumor is presented and relevant literature is discussed. [Arch Clin Exp Surg 2012; 1(3.000): 195-198]